The effect of octreotide, an analog of somatostatin, on bleomycin-induced interstitial pulmonary fibrosis in rats - Tug, Tuncer; Kara, Haki; Karaoglu, Aziz; Karatas, Fikret; Turgut, Nergiz Hacer; Ayan, Erhan; Tug, Esra (Taylor & Francis Ltd, 2013)
In this study, octreotide (OCT), a synthetic sonnatostatin analog, was tested for its beneficial effects in the prevention of interstitial pulmonary fibrosis (IPF) induced by bleomycin (BLM) in rats by histological examination and by evaluating tissue OH-proline levels. Thirty male Wistar rats were divided randomly into three groups: group I: intratracheal (i.t.) BLM (7.5 mg/kg, single dose) + saline solution [0.9% NaCl, subcutaneously (s.c.), once-daily for 7 days]; group II: i.t. BLM (7.5 mg/kg, single dose) + OCT acetate (82.5 mu g/kg, s.c., once-daily for 7 days); and the control group. At the end of the 7 days, lung tissues were excised and examined by histopathological methods. Levels of tissue hydroxyproline (OH-proline) were determined. BLM administration resulted in prominent histopathologic findings, such as diffuse alveolar damage and interstitial pulmonary fibrosis, as well as a significant increase in OH-proline level, as compared to controls. OCT application explicitly attenuated the histopathologic changes to a significant extent. OCT decreased paranchymal fibrosis and structural deformities in BLM-induced lung fibrosis. These results suggest that OCT administration to rats with BLM-induced IPF has a protective effect. Further studies are necessary to reveal the molecular mechanism(s) of OCT-induced protective effect.
Keywords: Bleomycin; pulmonary fibrosis; octreotide; rats